ClTI-Pep, um peptídeo sintético antimicrobiano bioinspirado no inibidor de tripsina da Cassia leiandra Benth., exerce efeito tóxico in vitro contra MRSA e Candida tropicalis resistente ao fluconazol - Araújo, Nadine Monteiro Salgueiro (2023)
Antimicrobial resistance, despite being neglected, has been a major global crisis in public health in recent decades. With the advent of the COVID-19 pandemic, the current concern with this topic has increased due to the indiscriminate use of antibiotics and antifungals, as they have increased the spread of multidrug-resistant strains worldwide. The limited number of effective drugs for the treatment of serious infections caused by fungi and bacteria results in thousands of deaths per year, associated with serious socioeconomic disorders. In this scenario, the scientific search for active molecules with biotechnological application in new anti-infective therapies is essential. Among the studies, special attention is given to the identification and strategic modification of antimicrobial peptides encoded in the structure of plant proteins. In a previous study, a Kunitz-type trypsin inhibitor (ClTI) with proven insecticidal and antimicrobial activity was purified from the seeds of Cassia leiandra Benth, an Amazonian medicinal plant. The objective of this work is, through the use of bioinformatics tools and in vitro tests, to provide information about the design, structure and activity of a new antimicrobial peptide bioinspired in the N-terminal sequence of ClTI. Called ClTI-Pep, a small, cationic and resistant synthetic peptide capable of penetrating microbial membranes was obtained. ClTI-Pep (162.03 μΜ) inhibited 100% of the growth, degraded the plasma membrane and DNA of methicillin- resistant Staphylococcus aureus (MRSA). Furthermore, ClTI-Pep showed synergistic action with fluconazole against resistant strain of Candida tropicalis. After treatment with the peptide alone or in synergism, the yeasts showed severe impairment of cell viability, such as strong oxidative stress, morphological changes, plasma membrane permeabilization, mitochondrial depolarization and positive labeling for apoptosis. The effect of ClTI-Pep on mammalian cell lines was also analyzed, and no sign of cytotoxicity or genotoxicity was verified. The data obtained bring to the scientific community a promising therapeutic candidate (ClTI-Pep) with strong and potentially safe antimicrobial action against strains of medical importance.